2009
DOI: 10.1007/s10484-009-9092-3
|View full text |Cite
|
Sign up to set email alerts
|

Time and Encoding Effects in the Concealed Knowledge Test

Abstract: Although the traditional ''lie detector'' test is used frequently in forensic contexts, it has (like most test of deception) some limitations. The concealed knowledge test (CKT) focuses on participants' recognition of privileged knowledge rather than lying per-se and has been studied extensively using a variety of measures. A ''guilty'' suspect's interaction with and memory of crimescene items may vary. Furthermore, memory for crimescene items may diminish over time. The interaction of encoding quality and tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
30
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 38 publications
4
30
2
Order By: Relevance
“…These findings are at odds with other deception studies which have found faster responses when participants were being truthful, compared to when they were producing a false claim (e.g., Kozel et al, 2005; Langleben et al, 2005; Spence et al, 2008; Seymour and Fraynt, 2009). This discrepancy, however, might stem from the realistic experimental paradigm we employed, which may have encouraged some of the participants to attempt to use strategies that would mislead the interrogator.…”
Section: Discussioncontrasting
confidence: 75%
“…These findings are at odds with other deception studies which have found faster responses when participants were being truthful, compared to when they were producing a false claim (e.g., Kozel et al, 2005; Langleben et al, 2005; Spence et al, 2008; Seymour and Fraynt, 2009). This discrepancy, however, might stem from the realistic experimental paradigm we employed, which may have encouraged some of the participants to attempt to use strategies that would mislead the interrogator.…”
Section: Discussioncontrasting
confidence: 75%
“…A specialized individual classification procedure that compared participants’ probe and irrelevant RT distributions led to a 0.93 hit rate with no false-alarms. Similar results have been reported in subsequent studies using related CKT test procedures and analyses (Seymour and Kerlin, 2008; Seymour and Fraynt, 2009; Verschuere et al, 2010; Visu-Petra et al, 2011). …”
Section: Introductionsupporting
confidence: 87%
“…This is in contrast to mock-crime procedures during which individual variations in memory, motivation, and attention can lead to the encoding of some probe items but not others (Carmel et al, 2003). Such variations may increase potential external validity, but could lead to the confounding of mock-crime effectiveness and the diagnostic accuracy of the test (Seymour and Fraynt, 2009). …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…These physiological responses are controlled by human autonomic nervous system, also be used as a reference lie detection [3].…”
Section: Introductionmentioning
confidence: 99%